# Show that p – 1 is a factor of p10 – 1 and also of p11 – 1.

let h (p) = 𝑝 10 − 1,and g(p) = 𝑝 − 1

Putting g (p) = 0 𝑝 − 1 = 0 𝑝 = 1

According to factor theorem if g(p) is a factor of h(p) , then h(1) should be zero

h(1) = (1)10 − 1 = 1 − 1 = 0

g (p) is a factor of h(p).

Now, we have h (p) = 𝑝 11 − 1, g (p) = 𝑝 − 1

Putting g (p) = 0 𝑝 − 1 = 0 𝑝 = 1

According to factor theorem if g (p) is a factor of h (p) ,

Then h(1) = 0

(1)11 – 1 = 0 hence g (p) the factor of h (p)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Polynomials - Zero to Hero42 mins  Genius Quiz | Polynomials40 mins  Zeros and Degrees of a Polynomial41 mins  Champ Quiz | Polynomials29 mins  Genius Quiz | Division of Algebraic Expressions37 mins  Introduction to Polynomials37 mins  Quiz | Imp. Qs. on Algebraic Identities65 mins  Basic understanding of Polynomials37 mins  Methods to find zeroes of a Polynomial-246 mins  Remainder Theorem and Factor Theorem38 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

Factorize:

x3 – 2x2y + 3xy2 – 6y3

RS Aggarwal & V Aggarwal - Mathematics

Factorize:

a2 + a – 3a2 - 3

RS Aggarwal & V Aggarwal - Mathematics

Factorize:

2a(x + y) -3b(x + y)

RS Aggarwal & V Aggarwal - Mathematics

Factorize:

8 – 4a – 2a3 + a4

RS Aggarwal & V Aggarwal - Mathematics

Factorize:

a2 + ab(b + 1) + b3

RS Aggarwal & V Aggarwal - Mathematics